Penerapan Interaktif dan Edukatif dalam Perancangan Digital Museum Budaya di Kabupaten Indramayu - Raihan Fahrezy; Desrina Ratriningsih (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The digital design of cultural museums with an interactive and educational approach in Indramayu Regency aims to present a modern, innovative, and interesting cultural preservation space. This concept was born from the urgent need for a means that are able to preserve, document, and promote local cultural wealth in the midst of the rapid flow of globalization. The lack of cultural literacy among the public, especially the younger generation, as well as the loss of historical objects due to inadequate storage facilities, are the main reasons for the importance of developing digital-based museums. Through an interactive approach, visitors can actively engage with cultural collections using advanced technologies such as augmented reality (AR), virtual reality (VR), and interactive multimedia. This technology provides an immersive, engaging, and personalized learning experience, so that visitors not only see, but also virtually experience the richness of the culture on display. Meanwhile, the educational approach is designed to create an informative, collaborative, and fun learning environment, which is highly relevant for learners and the younger generation as the successors of cultural preservation. Indramayu Regency, known for its long history, maritime traditions, and distinctive coastal culture, has great potential to become a center for cultural education. This digital museum will utilize digital technology to document cultural narratives in depth, so that it can be accessed not only by local people, but also national and international tourists. With its strategic location in the city center, the presence of this museum is expected to encourage the participation of the public and tourists in understanding, appreciating, and preserving the local culture of Indramayu. Apart from being an educational facility, this museum is expected to be able to become a driver of local tourism that makes a positive contribution to the economy of the surrounding community. Digital cultural museums are not only a place for preservation, but also a symbol of a strong regional identity, reflecting the synergy between technological innovation and commitment to cultural sustainability in the modern era.